2002
DOI: 10.1523/jneurosci.22-02-00536.2002
|View full text |Cite
|
Sign up to set email alerts
|

Anterograde Transport of Tumor Necrosis Factor-α in the Intact and Injured Rat Sciatic Nerve

Abstract: Tumor necrosis factor-alpha (TNF) appears as a key player at both central and peripheral terminals in early degenerative pathology and pain behavior after peripheral nerve injury. Recent studies suggest that TNF may be axonally transported and thereby contribute to these central and peripheral actions. To characterize this transport, we used a double ligation (DL) procedure that distinguishes between anterograde and retrograde flow to visualize the axonal transport of endogenous TNF compared with the neurotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 53 publications
7
77
2
Order By: Relevance
“…Several reports have described the expression of both TNFRI and TNFRII in rat DRG neurons (16)(17)(18)(19)(20)(21), but other studies identified only TNFRI in neurons, while localizing TNFRII in nonneuronal cells in the DRG (22,23). All of these findings support the hypothesis that treatment with etanercept or infliximab not only influences the inflammation process, but exerts antinociceptive effects by reducing direct pronociceptive actions of TNF␣ on nerve fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described the expression of both TNFRI and TNFRII in rat DRG neurons (16)(17)(18)(19)(20)(21), but other studies identified only TNFRI in neurons, while localizing TNFRII in nonneuronal cells in the DRG (22,23). All of these findings support the hypothesis that treatment with etanercept or infliximab not only influences the inflammation process, but exerts antinociceptive effects by reducing direct pronociceptive actions of TNF␣ on nerve fibers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the pro-inflammatory cytokine tumor necrosis factor ␣ (TNF␣) increases quickly at the site of peripheral nerve injury (Taskinen et al, 2000) and can increase glutamatergic synaptic strength (Bains and Oliet, 2007). However, TNF␣ does not qualify given evidence that it is not carried by retrograde transport to the DRG in injured nerves (Schafers et al, 2002) and is not restricted to primary afferents that are injured (Schafers et al, 2003). In contrast, the neurotrophin BDNF is a viable candidate by our criteria.…”
Section: Signals Initiating Synaptic Enhancementmentioning
confidence: 95%
“…Exogenous TNF may stimulate injured DRG by triggering one or more cascades, e.g., stimulating production of neurotrophins (Lindholm et al, 1987;Yoshida and Gage, 1992;Hattori et al, 1996,), which in turn may trigger sensitizing neuropeptides or further enhance DRG neuronal responses to capsaicin (Nicol et al, 1997). After sciatic nerve lesions, proinflammatory cytokines including TNF (Schäfers et al, 2002) and IL-6 (Murphy et al, 1995) are upregulated in lumbar DRG. These display synergistic algesic effects with TNF (Schäfers et al, 2001;Sweitzer et al, 2001).…”
Section: Sensitization Of Injured Primary Afferents To Tnfmentioning
confidence: 99%
“…Proinflammatory cytokines such as tumor necrosis factor-␣ (TNF) that are released after injury have been proposed as initiators (Wagner and Myers, 1996;Sommer and Schäfers, 1998;Sorkin and Doom, 2000). After peripheral nerve injury, DRG neurons robustly increase their expression of TNF (Schäfers et al, 2002). Exogenous TNF applied to intact or compression-injured DRG induces sustained mechanical allodynia (Homma et al, 2002).…”
Section: Introductionmentioning
confidence: 99%